Multi - Criteria Ranking of the Danube Water Quality on its Course Through Serbia - Mladenović-Ranisavljević, Ivana I.; Takić, Ljiljana; Vuković, Milovan; Nikolić, Đorđe; Živković, Nenad; Milosavljević, Peđa (Serbian Journal of Management, 2012)
This paper presents the results of multi-criteria ranking of the Danube water quality along its course through Serbia by using PROMETHEE/GAIA method. The ranking was based on the values of the water quality parameters measured at eight measuring stations on the Danube River in 2010. For the purposes of the investigation, ten water quality parameters that indicate physical, chemical and microbiological characteristics of water were selected. These parameters are also used in the WQI (Water Quality Index) methodology in determining the overall water quality. The results show that the water quality on the exit profile is better than the quality of the water at the entrance profile.
Keywords: water quality; ranking; PROMETHEE/GAIA; Danube